Microbiome Dynamics Associated With the Atacama Flowering Desert - Araya, Juan Pablo; González, Máximo; Cardinale, Massimiliano; Schnell, Sylvia; Stoll, Alexandra (Frontiers in Microbiology, 2020)
In a desert, plants as holobionts quickly respond to resource pulses like precipitation. However, little is known on how environment and plants modulate the rhizosphere-associated microbiome. As a model species to represent the Atacama Desert bloom, Cistanthe longiscapa (Montiaceae family) was selected to study the influence of abiotic and biotic environment on the diversity and structure of the microbiota associated to C. longiscapa rhizosphere. We analysed the rhizosphere and soil microbiome along a North-South precipitation gradient and between a dry and rainy year, by using Illumina high‐throughput sequencing. In the rhizosphere of C. longiscapa the microbiota clearly differs in composition and structure from the surrounding bulk soil. The fungal and bacterial communities respond differently to environmental conditions. The diversity and richness of fungal OTUs were negatively correlated with aridity, as predicted. Interestingly, the community structure was predominantly influenced by other soil characteristics (pH, organic matter content) but not by aridity. In contrast, diversity, composition, and structure of the bacterial community were not influenced by aridity or any other evaluated soil parameter. These findings coincide with the identification of mainly site-specific microbial communities, not shared along the sites. These local communities contain a group of OTUs, which are exclusive to the rhizosphere of each side and presumably vertically inherited as seed endophytes. Their ecological functions and dispersal mechanisms remain unclear. The analysis of co-occurrence patterns highlights the strong effect of the desert habitat over the soil- and rhizosphere-microbiome. The site-independent enrichment of only a small bacterial cluster consistently associated with the rhizosphere C. longiscapa further supports this conclusion. In a rainy year, the rhizosphere microbiota significantly differed from bulk and bare soil, whereas in a dry year, the community structure of the former rhizosphere approximates to the one found in the bulk. In the context of plant-microbe interactions in desert environments, our study contributes new insights regarding the importance of aridity in microbial community structure and composition, discovering the influence of other soil parameters in this complex dynamic network, which needs further to be investigated.